2018 IEEE Haptics Symposium (HAPTICS) 2018
DOI: 10.1109/haptics.2018.8357178
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a friction reduction based haptic surface at high frequency

Abstract: The influence of the vibration frequency on the friction reduction of an ultrasonic haptic surface has been reported in the literature. The models predict that increasing the frequency of the vibration leads to higher friction reduction at constant vibration amplitude, but this has not been reported experimentally. In this paper, we study the friction reduction on a prototype which can vibrate at low (66kHz) and high (225kHz) frequency. By estimating the Point of Subjective Equivalence between a standard at lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…where the α, p 0 , u 0 , and p s are the vibration amplitude of the plate, the atmospheric pressure, the gap at rest, and the pressing pressure, respectively. Although the model showed good fit with the results from human fingers and an artificial finger, it did not consider the effect of vibration frequency, which was shown to be an important factor in [13], [15], [16].…”
Section: Viewmentioning
confidence: 91%
See 2 more Smart Citations
“…where the α, p 0 , u 0 , and p s are the vibration amplitude of the plate, the atmospheric pressure, the gap at rest, and the pressing pressure, respectively. Although the model showed good fit with the results from human fingers and an artificial finger, it did not consider the effect of vibration frequency, which was shown to be an important factor in [13], [15], [16].…”
Section: Viewmentioning
confidence: 91%
“…where U , f , α, µ 0 , ν, and Ψ * are finger exploration velocity, vibration frequency, vibration amplitude, friction coefficient when the ultrasonic vibration is off, and the characteristic value of Ψ. Additionally, Giraud, et al [16] investigated the friction reduction on a vibrating plate at 66 kHz and 225 kHz. Both the friction measurements and psychophysical results showed that the ultrasonic friction reduction depended on the plate's acceleration.…”
Section: Viewmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanical behavior of skin has been extensively studied in the low-frequency end of the spectrum, where skin behaves mostly as an overdamped spring and damper system [24], [25], [26], [27] but little is known about the behavior in the ultrasonic range. Some models use a mass, spring, and damper series to capture the complex dynamics [28]. Recent measurements that rely on the self-sensing capabilities of ultrasonic friction modulation devices showed that skin behaves as a mass of ≈0.1 g in parallel with a damper of ≈20 N.s/m in the 30 to 40 kHz range [8].…”
Section: Biomechanics Of the Fingertipmentioning
confidence: 99%
“…A main design challenge in metamaterials is to tune band gaps to the desired carrier frequencies. For the application at hand, the band gaps should be set between 30 kHz and 225 kHz [20] in thin plates made of materials and dimensions relevant to surface haptics.…”
Section: Acoustic Metamaterialsmentioning
confidence: 99%